2018
DOI: 10.1080/10538712.2018.1486934
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Child Sexual Abuse: Impact, Risk, and Resilience in the Context of Culture

Abstract: Child sexual abuse is a problem with both a national and worldwide prevalence. In this review, the authors note that while empirical research has clearly shown the negative impact of child sexual abuse on social, psychological, and sexual functioning later in life, it has also been reported that some individuals remain asymptomatic despite a history of experiencing child sexual abuse. This implies that negative outcomes later in life are not inevitable and illustrates the critical need to elucidate how resilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 81 publications
3
58
0
4
Order By: Relevance
“…Lastly, with minor cross-cultural differences, the experience of non-consensual sex was related to greater levels of both anxiety and depression, less subjective well-being, less perceived intimacy with one's partner, and more loneliness. This corresponds with previous research (Hillberg et al, 2011;Maniglio, 2009;Sanjeevi et al, 2018). Lower perceived intimacy with one's partner was, for women, the variable most consistently associated with having had experienced non-consensual sex before or after the age of 18 years.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Lastly, with minor cross-cultural differences, the experience of non-consensual sex was related to greater levels of both anxiety and depression, less subjective well-being, less perceived intimacy with one's partner, and more loneliness. This corresponds with previous research (Hillberg et al, 2011;Maniglio, 2009;Sanjeevi et al, 2018). Lower perceived intimacy with one's partner was, for women, the variable most consistently associated with having had experienced non-consensual sex before or after the age of 18 years.…”
Section: Discussionsupporting
confidence: 90%
“…There is ample evidence that sexual abuse, whether experienced in childhood or in adulthood, is associated with an increased risk of various psychological, physical, interpersonal, and sexual problems (Hillberg, Hamilton-Giachritsis, & Dixon, 2011;Irish, Kobayashi, & Delahanty, 2010;Maniglio, 2009;Sanjeevi, Houlihan, Bergstrom, Langley, & Judkins, 2018). For example, in a systematic review of various longitudinal studies, and a meta-analysis across age groups, languages, and populations, Chen et al (2010) found a statistically significant association between sexual abuse and lifetime diagnoses of anxiety, depression, eating disorders, sleeping disorders, posttraumatic stress disorder, and suicide attempts.…”
Section: Non-consensual Sex and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative consequences of child marriage are awful. Negative health consequences of child marriage include poor maternal and reproductive health, increased risk of STIs, higher risk of intimate partner violence and more (Sarwade et al, 2019;Sanjeevi et al, 2018). This type of belief or misconception is only growing because of the lack of proper education.…”
Section: Introductionmentioning
confidence: 99%
“…La prevalencia glo bal estimada de la VSI está entre el 7,6 % y el 8,0 % en ho m bres y el 15,0 % y el 19,7 % en m ujeres (2)(3)(4)(5); la VSI con intento de penetración o penetración alcanza el 3,0 % en ho m bres y el 9,0 % en m ujeres (2). Según Stoltenborgh, van IJzendoor, Euser y Baker mans-Kranenburg (5), a nivel regional, la VSI m uestra un patrón de mayor prevalencia entre m ujeres, con excepción de Suramérica.…”
Section: Introductionunclassified